Motilin and its receptor are expressed in the dorsal horn in a rat model of acute incisional pain: Intrathecal motilin injection alleviates pain behaviors - Zhang, Yu; Zhao, Jun; Hu, Nan; Wang, Jing; Chen, Xi; Wang, Kaiyuan; Yin, Yiqing (Frontiers in Neuroscience, 2023)
Aims To observe the effects of intrathecal administration of motilin on pain behavior and expression of motilin (MTL)/motilin receptor (MTLR) in the spinal cord of a rat model of acute incisional pain. Methods An incisional pain model was established in rats using a unilateral plantar incision. The rats were also injected intrathecally with 1, 5, or 25 μg of motilin. The mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) were determined. MTL/MTLR expression in the spinal cord was detected by western blotting and immunofluorescence. The expression of MTL in the spinal cord, stomach, duodenum, and plasma was determined by enzyme-linked immunosorbent assay (ELISA). Results Motilin/motilin receptor were detected in the spinal cord. Spinal cord MTL/MTLR expression peaks at 2 h after modeling (P < 0.05) and start to decrease at 24 h (P < 0.05) to almost reach baseline levels at 72 h. The changes in gastric, duodenal, plasma, and spinal cord motilin levels correlated with MWT and TWL (all R2 > 0.82). The intrathecal injection of 1, 5, or 25 μg of motilin could increase the pain threshold of rats with incisional pain within 72 h in a dose-dependent manner. Conclusion This study showed for the first time that MTL/MTLR are expressed in rats’ spinal dorsal horn. Acute pain increased MTL/MTLR expression in the spinal dorsal horn. Also, for the first time, this study showed that motilin intrathecal injection alleviates pain in rat models of acute incisional pain. These results suggest that MTL/MTLR could be a novel target for the management of acute pain.